“The perfect storm”: community worker perspectives on the impact of COVID-19 on New York City immigrants and migrant-serving organizations - Hobbs, L. Ansley; Masoud, Dima; Cravero, Kathleen; Figueroa, Elisabeth Manipoud; Romero, Diana (Frontiers in Public Health, 2024)
Background Immigrants in New York City (NYC) have higher COVID-19 mortality than the general population. While migrant-serving organizations (MSOs) provide access to a breadth of services, they are disproportionately impacted by the COVID-19 pandemic due to staffing limitations, funding cuts, and resource limitations of communities served. Methods Six focus-group discussions were conducted to explore the experiences of MSOs in NYC during the COVID-19 pandemic from November 2021 to March 2022. Study participants csomprised a subsample of survey respondents from a larger study identified via lists of MSOs. Results Twenty-seven organizational representatives from 11 MSOs across NYC participated in the discussions. In addition to providing information on communities served, services offered, and organizational characteristics, the following themes emerged from the convenings: mental health challenges and resources needed for immigrants; immigration-related challenges; factors exacerbating hardships for immigrants during COVID-19; interorganizational collaborations and partnerships; policy change; and needs/requests of MSOs. MSOs provide a wide range of services as non-profit organizations and use interorganizational collaboration to improve service delivery. The proximity of MSOs to immigrant communities helps providers understand the needs of immigrants relating to the COVID-19 pandemic and factors that shape telehealth services. Conclusion MSOs are important providers and advocates for immigration policy in the US given their relationship with the populations they serve. These findings have implications for how to support MSOs that serve immigrants in NYC. Strategies to achieve this include timelier availability and exchange of information, policies, and research as well as strengthening the experience-based advocacy of these groups.